Transcription factor NFκB regulates the expression of the histone deacetylase SIRT1 - Katto, Judith; Engel, Nicole; Abbas, Wasim; Herbein, Georges; Mahlknecht, Ulrich Rudolph (Clinical epigenetics, 2013)
The NAD-dependent protein deacetylase SIRT1 has a wide range of different targets, which may be regulated either directly through deacetylation and thus potentially altering their activity or localization or indirectly by deacetylation of histones, which in turn alters their transcription rate and availability. SIRT1 is therefore involved in the regulation of many different and fundamental cellular processes such as apoptosis, metabolism, differentiation and cell cycle arrest. It is also involved in the regulation of resistance of cells against oxidative stress and longevity under conditions of caloric restriction. Even though the targets and role of SIRT1 have been studied quite intensively, only little is known about the mechanisms affecting SIRT1 transcriptional regulation. The nuclear factor NFκB is a well-studied and widely known transcription factor, which is involved in the regulation of many important cellular activities. The regulation of NFκB by SIRT1 has been reported recently, but it is, however, still unknown whether a feedback mechanism affects the regulation of SIRT1 too, particularly in view of the fact that putative NFκB binding sites within the SIRT1 promoter suggest just that.
Gesehen am 22.04.2021